STRATEGI PROMOSI TERHADAP PENGEMBANGAN PANTAI LAKEY SEBAGAI DESTINASI WISATA BERBASIS BAHASA INGGRIS - Ita Purnama; Fenny Aryani (Universitas Putera Batam, 2019)
This study aims to determine the significant effect of promotion strategies on the development of Lakey beach as an English-based tourism destination. Lakey Beach is famous for its beautiful beaches and its waves are hampered by its development due to several factors including promotional activities that are rarely carried out by the relevant government, facilities and accommodations that are still incomplete and English language skills and proficiency at Lakey Beach are still lacking. English language skills for guides or people who are on the beach are very influential on the satisfaction of tourists, especially foreign tourists when visiting. The research method used was associative research where the research location was located on Lakey Beach, Hu’u Dompu. Population in this study were all local and foreign tourists who had visited Lakey Beach with total sample of 96 people. Variable Measurement The research in this study uses a score that refers to the use of the Likert scale with the data analysis technique used, namely simple linear regression analysis using the equation, namely: Y = a + bx. The results of the study show that the Promotion Strategy has a significant influence on Tourism Development Based on English. This is evidenced by the value of tcount> t table which is 10.961> 1.985 with a significance value of 0.000 smaller than 0.05 (0.000 ≤ 0.05).